Application of The Nutrient Film Technique (NFT) Hydroponic System Water Spinach Cultivation (Ipomoea sp.) - Audela Oktavira; Delvia Suarman; Fajri Rifyant; Resti Fevria (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
The hydroponic system is one of the most popular forms of plant cultivation in recent times because it can produce higher and cleaner quality yields than using soil. The NFT hydroponic system is one of the most widely applied hydroponic techniques because of the easier way to control plants and water and nutrient needs can be met properly. The purpose of this study was to apply the Nutrient Film Technique (NFT) hydroponic system to water spinach plants and to determine the growth results produced in this hydroponic system technique using AB mix nutrition. The research method used in this study was an experimental method. with a qualitative descriptive analysis that is observing the comparison of the growth of kale plants per week through measurement parameters from aspects of plant height and number of plant leaves. Based on the results of the study, at the age of 18 days, kale plants resulted in the growth of plant height with an average of 13.6 cm and an average number of leaves of 5 leaves, thus proving that the NFT hydroponic system gave good results on the growth of water spinach. Keywords : Hydroponic, NFT, Water Spinach, Cultivation, Plant